Specific adsorption of cytochrome C on cardiolipin-glycerophospholipid monolayers and bilayers - Domènech, Oscar (Langmuir : the ACS journal of surfaces and colloids, 2007)
In this study, we examined the adsorption of cytochrome c (cyt c) on monolayers and liposomes formed from (i) pure 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE), or cardiolipin (CL) and on (ii) the more thermodynamically stable binary mixtures of POPE/CL (0.8:0.2 mol/mol) and POPC/CL (0.6:0.4 mol/mol). Constant surface pressure experiments showed that the maximum and minimum interactions occurred in the pure CL (anionic phospholipid) and the pure POPE (zwitterion) monolayers, respectively. Observation by atomic force microscopy (AFM) of the images of Langmuir-Blodgett (LB) films extracted at 30 mN m-1 suggests that the different interactions of cyt c with POPE/CL and the POPC/CL monolayers could be due to lateral phase separation occurring in the POPE/CL mixture. The competition between 8-anilino-1-naphthalene sulfonate (ANS) and cyt c for the same binding sites in liposomes that have identical nominal compositions with respect to those of the monolayers was used to obtain binding parameters. In agreement with the monolayer experiments, the most binding was observed in POPE/CL liposomes. All of our observations strongly support the existence of selective adsorption of cyt c on CL, which is modulated differently by different neutral phospholipids (POPE and POPC)